Madrasah Principal Leadership in Developing Teacher Careers at MIN 1 Labuhan Batu - Adolina Adolina; Inom Nasution; Mara Samin Lubis (Journal of General Education and Humanities, 2025)
This study aims to analyse the role of madrasah principal leadership in fostering teacher career development at MIN 1 Labuhanbatu. The background of the study highlights the persistent challenges faced by madrasah teachers in achieving the expected qualifications and professional competencies, often hindered by the lack of strategic and effective leadership. This research adopts a qualitative phenomenological case study approach, involving one madrasah principal and three teachers as participants. Data were collected through in-depth interviews, direct observation, and document analysis, and were analysed using Miles and Huberman’s interactive model of qualitative data analysis. The findings reveal that a firm yet transparent leadership style, characterised by inclusive decision-making and consistent motivation from the principal, plays a significant role in creating a positive and supportive work climate. Such leadership enhances teacher engagement, commitment, and continuous professional growth. The study concludes that effective leadership in Islamic schools is a critical factor in improving educational quality through the sustainable development of teacher careers.